In Their Own Words… - (GAATW), Global Alliance Against Traffic in Women (Anti-Trafficking Review, 2018)
The Editors approached service providers members of the Global Alliance Against Traffic in Women (GAATW) with a request to speak to people who are using their services and ask them about the difficulties they are currently facing, their hopes for the future, or anything else they want to share with the journal audience. The responses below were translated by the service providers or GAATW staff and have been edited only for clarity.